Determinan Kinerja Keuangan Pemerintah Daerah dengan Belanja Modal sebagai Variabel Moderating (Studi Empiris Pada Kabupaten/Kota di Provinsi Jambi) - Hajar, Ibnu; Afrizal, Afrizal; Fatimah, Fatia; Wahyu, Milde; Solihat, Iis; Simarmata, Joner (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Regional Budget of Revenue and Expenditure Management in Jambi Province is not yet optimal, due to the inadequate ratio between direct and indirect expenditure. The purposes of this research are to: 1) examine the impact of District Own-Source Revenue and equalization fund 1individually towards local government financial performance on regency/city of Jambi Province 12016-2020; 2) examine the significance of District Own-Source Revenue and equalization fund impact simultaneously towards local government financial performance on regency/city of Jambi Province 12016-2020; dan 3) examine whether capital expenditures is capable to become the moderating variable 1between District Own-Source Revenue and equalization fund with local government financial performance on regency/city of Jambi Province 2016-2020. This research uses the type of causal research. The population of this research is regency/city government in Jambi Province which consists of 9 regencies and 2 cities. Data analysis technique that is used in this research is multiple linear regression analysis. The result indicates that: 1) individually District Own-Source Revenue gives positive and significant impact towards local government financial performance, meanwhile equalization fund gives negative and significant impact towards local government financial performance; 2) both District Own-Source Revenue and equalization Fund significantly impact local government financial performance; and 3) based on residual test results, it shows that capital expenditures is the only variable that is able to moderate the correlation between District Own-Source Revenue towards local government financial performance.